APPLICATION OF CAUSAL FORECASTING METHOD TO FORECAST SHALLOT PRODUCTION IN NORTH SUMATRA PROVINCE - Zebua, Feber Wati; Fairus, Fairus; Amelia, Amelia (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Shallot are one of the superior horticultural commodities that has a great influence on the economic value and daily needs of society. The province of North Sumatra is a strategic region for producing shallot, making the province the eighth largest producer of shallot in Indonesia. The need and consumer demand for shallot along with the increasing population is a problem, as by 2021 the amount of shallot production in the household sector will only be met by 11% in the North Sumatra province. The authors are therefore interested in studying the factors that influence shallot production and predicting the amount of shallot production in the future North Sumatra province. The source of data the research was carried out by the Agricultural Department of the Province of North Sumatra. The study was conducted using Causal Forecasting and ARIMA methods. The causal forecasting method used is the econometric method. The econometric method is a method for analyzing and predicting future conditions by finding and measuring several important independent variables and their influence on the variables. Dependents are observed. The ARIMA method is used to predict exogenous variables from the results of the analysis performed. Based on the analysis, it is obtained that the factors affecting the amount of shallot production are the quantity of productivity and the extent of the onion harvest. The greater the amount of productivity and the size of the harvest, the more shallot production will increase. The result of the production forecast obtained is the lowest amount of shallot production occurred in April 2022 at 5212,763 tons and the highest amount produced on the onion occurs in March 2023 at 6502,112 tonnes and the average monthly amount of production is 5856,886 tons.